Atlas of health-related infrastructure in discrete indigenous communities - Bailie, Ross.; Australia. Aboriginal and Torres Strait Islander Commission. National Housing and Infrastructure Centre (Melbourne : Aboriginal and Torres Strait Islander Commission (ATSIC), National Housing and Infrastructure Centre, 2002)
Source of information for the maps is the 1999 Community Housing and Infrastructure Needs Survey (CHINS); maps show location and some statistics for housing, water supply, flooding and ponding, sewerage, rubbish disposal, power supply, communications and transport, roads within communities, education, health facilities and health personnel.
Keywords: Aboriginal Australians -- Housing -- Atlases; Aboriginal Australians -- Health and hygiene -- Atlases; Aboriginal Australians -- Social conditions -- Atlases; Health services - Community health centres; Community development - Infrastructure and municipal services - Energy supply; Community organisations - Housing; Community development - Infrastructure and municipal services; Water supply; Outstations / Homelands movement - Infrastructure - Sewage and sanitation; Australia